Pemetaan Model Brand Identity Prism Untuk Peningkatan Daya Tarik Wisata Pantai Widuri - Saputri, Wulan Feriana; Alifahmi, Hifni (Universitas Prof. Dr. Moestopo (Beragama), 2024)
This research is motivated by issues found relate nonoptimal visits to tourist destinations in Pemalang district, Widuri Beach is located in the city center and is seen as having the potential to be developed into a leading tourist destination. and it is necessary to increase the Marketing and Tourism Industry of Pemalang Regency. By mapping the Brand Identity Prism model, this research is expected to provide guidance in developing Widuri beach tourist attraction and increase the number of tourist visits to the area. Data were collected through observation, interviews and documentation studies. Observations were made to directly observe the condition of Widuri Beach and existing facilities. Interviews were conducted with related parties such as tourism managers, and tourists who have visited Widuri Beach. Documentation studies were also carried out by collecting data and information related to tourism development in Pemalang Regency. Based on the research results, it is known that Widuri Beach in Pemalang Regency has great potential to be developed as a tourist destination. Natural beauty and prominent physical features are the main attraction; however, improvements are needed in the maintenance of physical facilities and destination cleanliness. Development of additional attractions such as additional rides or routine activities can increase public interest in visiting this beach. The management of tourist destinations has been carried out professionally, and the brand identity of Widuri Beach needs to be further strengthened and developed.